Modelagem de mudanças espaço-temporais de ambientes glaciais dos Andes do Sul - Peru - Cayo, Efrain Yury Turpo (2018)
Tropical glaciers are important solid freshwater reserves, represent excellent indicators of climate change, water suppliers in regions with scarce rainfall and regulators of the hydrological regime and have high temporal dynamics. These glaciers are in a process of decrease caused by climate change. In this context, this research has as main objective to evaluate and to model the spatio-temporal changes of glacial environments in the Andes Mountains of Southern Peru, evaluating the possible relationships in the change trends among glaciers, the coverings of Andean Wetlands (Bofedal) and water bodies (proglacial lakes). These tasks were accomplished by different methods of digital processing of satellite imagery and Digital Elevation Model (DEM) on the platform of cloud processing Google Earth Engine (GEE) and other applications. With the propose of mapping at large scale and conducting a cellular automata-bases modeling experiment, different spectral indices and time series analyses in the Landsat satellite images of the past 32 years and MODIS time series images of the last 17 years were employed ending up with a forecast for the time horizon of 2032. The results of the analyses indicate high dynamics in glacial environments in dry outer tropics compared to the southern wet outer tropics. Most of the mountain ranges found increasing surface extension of Andean Wetlands and water bodies and retreat of glaciers. We propose the Normalized Difference Fraction Index Bofedal (NDFIb) index, an adaptation of the Normalized Difference Fraction Index (NDFI), showing improvements in mapping the extent of Andean Wetlands. In the spatial dynamic modeling of glacial environments based on the cellular automata paradigm, simulation results achieved an acceptable accuracy (ISF = 0.829 in the 5x5 window), which may be an alternative to deterministic models. The results make an important contribution to the study of the dynamics of glacial environments.